Crashworthiness Analysis of S-Shaped Structures Under Axial Impact Loading - Esmaeili-Marzdashti,Sobhan (2017)
Abstract To mitigate shock forces in collision events, thin-walled members are used as energy absorber. In this article, crashworthiness of single-cell and multi-cell S-shaped members with various cross-sections including triangular, square, hexagonal, decagon and circular were investigated under axial dynamic loading using finite element code LS-DYNA. Furthermore, crashworthiness of the S-rails with the same outer tubes and different inner ones was studied as well. The multi-cell members employed in this task were double-walled tubes with several ribs connecting the inner and outer tubes together. Modified multi criteria decision making method known as complex proportional assessment (COPRAS) was used to rank the members using three conflicting crashworthiness criteria namely specific energy absorber (SEA), peak crash force (Fmax) and crash force efficiency (CFE). Moreover, the multi-cell S-shaped members were found to perform better than single-cell ones in terms of crashworthiness. In addition, the multi-cell S-rail with decagonal cross-section was found as the best energy absorber, and also the S-rail having the same inner and outer tube with decagonal cross-section displayed desirable crashworthiness performance. Optimum geometry of this S-rail was eventually obtained from the parametric study.